REAFIRMASI POSISI PEREMPUAN: Mengulas Pandangan Lama - Tri Handayani (Al-Dirayah, 2018)
Talk about women since ancient times is endless. Every conversation about women shows that women occupy the most respected positions, but on the other hand women will occupy the lowest position, both in social, cultural, economic, political, and even religious views. In the Islamic tradition, as revealed by Yunahar Ilyas (1997), there are four types that are believed to be the way of human creation; 1. From the ground (the creation of Adam); 2. Created from (rib) Adam (creation of Eve); 3. Created through a mother with a fatherless pregnancy, both legally and biologically (the creation of the Prophet Isa); 4. Created through pregnancy with father biologically and law or at least biologically only (creation of humans other than Adam, Eve, and Isa). The emphasis of this paper lies in the old view, namely about the creation of air. So the question arises from this picture whether Eve was created from the ground, the same material as Adam was created or from the part of Adam's body?